Differential Contributions of Empathy to Math Achievement in Women and Men - Ghazy, Nermine; Ratner, Eleanor; Rosenberg-Lee, Miriam (Frontiers in Psychology, 2019)
Mathematics forms a foundation for the science, technology, engineering and mathematics (STEM) fields. While considerable work has identified the individual cognitive and external systemic factors that influence math achievement, less is known about personality-like traits that might contribute to success in mathematics, especially among women. This study examines two such traits: systemizing – the tendency to analyze systems and extract underlying rules that govern its behavior – and empathizing – the ability to identify with another’s emotions and respond appropriately. Recently Escovar, Rosenberg-Lee, Uddin, and Menon [Scientific Reports, 6, 23011 (2016)] found that empathizing was a negative predictor of math skills in children, especially among girls, suggesting that women with higher empathy might be particularly disposed to lower math performance. In the first study 142 participants (71 female) completed two standardized measures of math achievement and questionnaires to gauge the tendency to empathize and systemize. Surprisingly, higher empathy was associated with better math performance in women, while men displayed the expected pattern of lower empathy being related to higher math scores. In a second study, we extend this finding in women (n = 121) to show that individuals who report higher mathematics achievement in university level course work also have higher empathy scores. Further, while positive attitudes towards mathematics tended to decline from elementary school to college, women whose attitudes increased had higher empathy scores than those who declined. Together these results suggest that while the tendency to empathize is associated with worse math performance in childhood, it may become a protective factor as women progress through their mathematics education.